Optimalisasi Pajak Digital di Era Ekonomi Kreator: Tantangan dan Peluang bagi Pemerintah Indonesia - Nur Khiba Sania Sania; Imahda Khoiri Furqon (Journal Axegnal: Tax And Economic Insights Journal, 2026)
The growth of the creator economy in Indonesia from 2020 to 2025 has shown a significant upward trend in both the number of actors and the economic value generated. This transformation encourages the government to optimize digital taxation policies as a new source of state revenue. This study focuses on the challenges and opportunities in implementing digital taxation within the creator economy. A qualitative method is applied through literature studies and content analysis of relevant secondary sources. The findings indicate that the optimization of digital taxation in Indonesia is still hindered by incomplete regulations, limited digital monitoring technology, low tax literacy among creators, and the absence of a specific taxation framework for cross-platform income generation in the creator economy. Conversely, the large digital market, widespread internet use, and technological advancements in tax administration such as big data analytics and the PMSE system create strategic opportunities to expand the tax base. This study contributes to the existing literature by addressing the research gap that previously focused more on e-commerce rather than the creator economy. The results highlight the need for regulatory harmonization, improved tax education, and strengthened digital infrastructure to ensure sustainable tax revenue and fiscal sovereignty in Indonesia’s growing digital economy.